2019
DOI: 10.1093/nop/npy059
|View full text |Cite
|
Sign up to set email alerts
|

BDNF, COMT, and DRD2 polymorphisms and ability to return to work in adult patients with low- and high-grade glioma

Abstract: Background Cognitive and language dysfunction is common among patients with glioma and has a significant impact on survival and health-related quality of life (HRQOL). Little is known about the factors that make individual patients more or less susceptible to the cognitive sequelae of the disease. A better understanding of the individual and population characteristics related to cognitive function in glioma patients is required to appropriately stratify patients, prognosticate, and develop mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Our results compare well with previously published literature. Altshuler et al studied the association of genetic alterations with neurocognitive function and ability to return to work in a series of 34 patients with gliomas WHO grades II and III who did not receive adjuvant treatment following surgery [40]. Here, 42% of the patients returned to work within three months following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our results compare well with previously published literature. Altshuler et al studied the association of genetic alterations with neurocognitive function and ability to return to work in a series of 34 patients with gliomas WHO grades II and III who did not receive adjuvant treatment following surgery [40]. Here, 42% of the patients returned to work within three months following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that COMT can upregulate tumor suppressor genes by the PI3K/Akt pathway and inhibit the growth and invasion of cancer cells (31). COMT mutations are significantly correlated with cognitive impairment in brain tumor patients (32), and this conclusion is also applicable in glioma patients (33). Therefore, COMT may have a potential protective effect, and mutations in this gene may influence prognosis by affecting cognitive ability.…”
Section: Discussionmentioning
confidence: 96%
“…In an earlier study we discussed the notion of cognitive functioning as a marker for diffuse tumor infiltration, and the option that cognitive functioning and survival are determined by overlapping germline and somatic molecular-genetic factors. 3 Indeed, several studies already showed that multiple SNPs (single nucleotide polymorphisms) are associated with neurocognitive performance 26 , 27 and cognitive impairment is found to occur more frequently in glioma patients with wild-type IDH1 tumor status when compared to those with a mutant IDH1 tumor status. 28 , 29 A more recent publication of Daniel et.…”
Section: Discussionmentioning
confidence: 99%